The Implementation of the Pancasila Student Profile in Learning Moral Creeds for Class 12 Students at MAN 1 East Lampung - Ardiansah, Rahmad Ivan; Jaenullah, Jaenullah; Arifin, M. Zainal (International Journal on Advanced Science, Education, and Religion, 2025)
The Pancasila student profile is a project in the independent curriculum to shape the character of students in accordance with the philosophy of the Indonesian nation, namely Pancasila. The moral aqidah subject at MAN 1 East Lampung is a means for the process of implementing the values of the Pancasila student profile to students which includes six elements in it. In this research, a qualitative field approach was used, the researcher chose sampling subjects to obtain information related to the research. The research steps begin with the process of data collection, on-site observations, interviews and documentation. The results of this research are that in the implementation process the teacher acts as a facilitator and controls the development and extent of students' understanding in the learning process in the classroom. With the learning method used, the process of implementing the Pancasila student profile takes place in learning moral beliefs for students at MAN 1 East Lampung. In this way, the student's character is in accordance with the six elements in the Pancasila student profile, becoming a person who behaves well in the school, family and community life.